PENERAPAN PRINSIP GOOD GOVERNANCE DALAM MANAJEMEN ORGANISASI KECAMATAN TATANGA KOTA PALU - Nirmala Apsari (Bajang Institute, 2024)
This study examines the implementation of Good Governance principles in the organizational management of Tatanga District, Palu City, with a focus on accountability, participation, responsiveness, and professionalism. The research employs a qualitative approach, utilizing interviews, observations, and document analysis to gather data. The findings reveal significant challenges in applying these principles effectively. Accountability mechanisms are found to be weak, with limited transparency in financial reporting and performance evaluation. Public participation in decision-making processes remains low, hindering community involvement in local development planning. The district government's responsiveness to public complaints and urgent issues is notably slow, affecting service delivery. Additionally, the professionalism of district staff requires improvement, with inadequate technical competencies and limited continuous professional. development programs. The study concludes that substantial efforts are needed to enhance these aspects of governance in Tatanga District. Recommendations include developing a more transparent accountability system, increasing public participation forums, implementing a more responsive complaint handling mechanism, and establishing comprehensive staff competency development programs. These improvements are crucial for enhancing the quality of public services and promoting community welfare in Tatanga District.